2016
DOI: 10.5430/wje.v6n3p10
|View full text |Cite
|
Sign up to set email alerts
|

Teachers’ Perceptions and Practices of Written Feedback in Higher Education

Abstract: This mixed-methods research aimed to understand the practices and perceptions of teachers regarding written feedback. For this purpose, a survey was administered to 150 teachers forming a non-probability sample, who were working in various universities in Karachi. The disciplines chosen for the study included nursing, applied linguistics, medicine and education departments in institutes of higher education situated in Karachi. Before sampling, initial screening was done to obtain a list of institutes which pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
49
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(53 citation statements)
references
References 22 publications
4
49
0
Order By: Relevance
“…The results obtained from both on-script feedback comments and interviews disclosed that the supervisors generally used the directive feedback language most dominantly in their feedback provision as compared to expressive feedback. This nding is consonant with previous works in which directive feedback has been found pervasiveness in the provision of feedback (Gul et al, 2016;Leng, 2014;Lucero, Fernández & Montanero, 2018;Yenus, 2018). Conversely, the study done by Kumar and Stracke (2007) showed that the directive and expressive feedback functions shared equal status in the feedback provision of the supervisors.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The results obtained from both on-script feedback comments and interviews disclosed that the supervisors generally used the directive feedback language most dominantly in their feedback provision as compared to expressive feedback. This nding is consonant with previous works in which directive feedback has been found pervasiveness in the provision of feedback (Gul et al, 2016;Leng, 2014;Lucero, Fernández & Montanero, 2018;Yenus, 2018). Conversely, the study done by Kumar and Stracke (2007) showed that the directive and expressive feedback functions shared equal status in the feedback provision of the supervisors.…”
Section: Discussionsupporting
confidence: 92%
“…Concerning language functions of written feedback, a couple of studies showed the prevalence of direct feedback provision on students' errors (Gul et al, 2016;Lucero, Fernández & Montanero, 2018). Besides, Yenus (2018) carried a study on language functions of supervisors' written feedback to students' thesis at Bahir Dar University, Ethiopia.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is also missed opportunity for learning through feedback, as evidence identifies that some academics have limited skills, and knowledge, or they perceive summative assignments as a marking task, rather than a crucial and insightful opportunity to positively influence personalised learning (Orrell, 2006). Other issues are related to embedded perceptions that students don't read their feedback because students are only focused on their grade and ignore the written feedback provided to them (Iqbal et al, 2014, Gul et al, 2016.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies conducted in Pakistani healthcare institutions explored feedback in the form of teachers" written comments on assessments and feedback on assessments only 15,16 , whereas in our study participants" experiences showed that they got information about their performance in ways much beyond written comments or feedback on assessments only.…”
Section: Discussionmentioning
confidence: 73%